Creep experiments and theoretical research of shale hydration damage based on NMR. Issue 13 (3rd November 2022) - Wang, Ping; Huang, Hai; Qu, Zhan; Wang, Peng tao; Han, Qiang; Ren, Zongxiao
Abstract: Damage mechanics and rheological mechanics are combined to solve the shale sidewall instability problems in oil and gas drilling engineering. The microcracks in the shale sidewall rocks and the rheological effect caused by the physical and chemical interplay between the inflow fluid and underground fluids are studied. According to nuclear magnetic resonance analysis, mechanics experiments and theoretical analysis, the hydration damage variables characterized by the NMR T2 spectrum are established. A creep model for shale considering hydration and creep damage is proposed. It shows the creep characteristics and evolution process from spreading, propagation, and transfixion to the collapse of the initial imperfection, after the hydration of shale sidewall surrounding rocks. It is the basic theory proposed to study side wall creep damage instability. The results show that the creep of the shale is a nonlinear rheology. Due to the influence of hydration, the pore structure of the rock sample was redistributed, and the signal amplitude of the measured T2 curve changed significantly. During the course of the loading process, the rock samples undergo three stages: decay creep, constant velocity creep and acceleration creep. The creep strain of the sample increased with increased moisture content, and the creep rate increased with increased stress. Graphical Abstract: Graphical Abstract: UF0001